Effector identification in the pine pathogen Dothistroma septosporum - Hunziker, L.; Mesarich, C.H.; McDougal, R.L.; Bradshaw, R.E. (New Zealand Plant Protection, 2016)
Effectors are molecules produced by plantassociated organisms such as fungal pathogens that facilitate infection of specific plant hosts Some effectors directly or indirectly suppress host defence responses while others help to mask the foreign invader from recognition by the plant Plants can also recognise and respond to specific effectors to mount a resistance response Thus the study of effectors is important for an understanding of plantpathogen interactions Dothistroma septosporum causes Dothistroma needle blight (DNB) a conifer disease of worldwide importance In this study effector genes specific to the D septosporumPinus radiata interaction were identified A bioinformatics pipeline was employed to predict effector candidates on the basis of characteristics such as secretion from the fungus and expression in planta Using this pipeline 55 effector candidates for future analysis were identified